2022
DOI: 10.1155/2022/2035808
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Analysis of Pyroptosis-Related Long Noncoding RNA Immune Infiltration and Prediction of Prognosis in Patients with Colon Cancer

Abstract: Colon cancer (CC) is one of the most prevalent malignant tumours of the alimentary canal. It is unclear whether pyroptosis-related lncRNA expression is correlated with CC prognosis. We discovered 20 pyroptosis-related lncRNAs that were expressed differently in CC and normal colon tissues in our investigation. Based on differentially expressed genes (DEGs), we grouped all CC patients into two categories (Clusters 1 and 2). Cluster 1 was shown to be connected with a higher overall survival rate, upregulated expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 62 publications
(70 reference statements)
0
8
0
Order By: Relevance
“…More importantly, previous studies have confirmed that the NRlncRNA signature also can be used to predict the prognosis of tumors. For instance, the NRlncRNAs have vital functions in Colon Cancer, and the signature composed of NRlncRNAs can predict the prognosis of Colon Cancer (CC) and be used to customize CC treatment in the future ( Liu et al, 2022 ). However, the relationship between NRlncRNAs and STS is still unknown.…”
Section: Discussionmentioning
confidence: 99%
“…More importantly, previous studies have confirmed that the NRlncRNA signature also can be used to predict the prognosis of tumors. For instance, the NRlncRNAs have vital functions in Colon Cancer, and the signature composed of NRlncRNAs can predict the prognosis of Colon Cancer (CC) and be used to customize CC treatment in the future ( Liu et al, 2022 ). However, the relationship between NRlncRNAs and STS is still unknown.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Luo et al studied the association of lncRNAs with stomach adenocarcinoma, focusing on a twelve NRL signature which included LASTR, one of the lncRNAs identified in this work as NRL for KIRC [ 40 ]. Liu et al studied lncRNAs in colon cancer and identified MYOSLID as associated to pyroptosis, linking this lncRNA to regulation of SKP1 expression via MIR-589-5p and to the miR-29c-3p-mcl-1 axis [ 41 ]. The function of lncRNAs in sequestering and inactivating one or more miRNA species was studied also in the necroptosis response in HCC [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several recent studies have proposed prognostic models for COAD [22][23][24]. However, the studies' predictive performances have not been validated in COAD, and the differences in immune infiltrating cells and immune checkpoint blockade-, immune checkpoint-, and m6A-related genes between the high and low risks of the prediction model were not analyzed.…”
Section: Discussionmentioning
confidence: 99%